Efficacy of Physical Exercise on the Quality of Life, Exercise Ability, and Cardiopulmonary Fitness of Patients With Atrial Fibrillation: A Systematic Review and Meta-Analysis - Shi, Shuqing; Shi, Jingjing; Jia, Qiulei; Shi, Shuai; Yuan, Guozhen; Hu, Yuanhui (Frontiers in Physiology, 2020)
Objective: Physical exercise is recommended to help prevent lifestyle diseases. The present study was designed to quantify the efficacy of physical exercise on the quality of life (QoL), exercise ability and cardiopulmonary fitness of patients with atrial fibrillation (AF). Method: A comprehensive systematic literature search was performed in Medline, Embase, Cochrane Library, Web of Science and PubMed databases (from 1970 to December 1st, 2019) for randomized controlled trials (RCTs) comparing physical exercise combined with AF routine treatments to routine treatments alone. The meta-analysis was conducted following PRISMA guidelines. Our main outcomes were QoL (measured by the Short-Form 36 scale, SF-36), exercise ability (measured by the 6-minute walk test, 6MWT) and cardiopulmonary fitness (measured by peak oxygen uptake and resting heart rate). Quality assessments were conducted using the Cochrane Collaboration tool. Results: Twelve trials involving 819 patients met the criteria for analysis. The results showed that physical exercise improved the QoL by enhancing physical functioning [standardized mean difference (SMD)=0.63, 95%CI: 0.18 - 1.09; p=0.006], general health perceptions (SMD=0.64, 95%CI: 0.35 - 0.93; p<0.001) and vitality (SMD=0.51, 95%CI: 0.31 - 0.71; p<0.001); increased exercise ability by improving the 6MWT performance (SMD=0.69, 95%CI: 0.19 - 1.119; p=0.007); and enhanced peak VO2 (SMD=0.37, 95%CI: 0.16 - 0.57; p<0.001) while reducing resting heart rate (SMD=-0.39, 95%CI: -0.65 - -0.13; p=0.004). In addition, meta-regression analysis showed that training mode (p physical functioning=0.012, p general health perceptions=0.035) and training duration (p=0.047) were the main factors of an intervention that influenced the effect size. Following sub-group analysis, we found that aerobics, Yoga and longer training durations (≥60 min) showed larger improvements. Conclusion: In summary, our meta-analysis shows that physical exercise has a positive effect on the QoL, exercise ability and cardiopulmonary fitness in AF patients. When physicians offer exercise recommendations to AF patients, they should consider both the training mode and training duration to achieve maximum results.